Penerapan Metode Analytical Hierarchi Process (AHP) Dalam Menentukan Tingkat Kerentanan Stunting (Gizi Buruk) Desa Di Kecamatan Juhar - Juliansen Saragih; Agustina Simangunsong (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
In February, measurements of weight and height of children born in 2016-2020 were carried out in 25 villages. The data collection conducted by Juhar District officers was only based on height (TB) and weight (BB), these two criteria did not represent the determination of a child susceptible to stunting considering several other causes of stunting. Determination of the level of vulnerability to stunting can be studied using a Decision Support System with the Analytical Hierarchy Process (AHP) method. , and parenting styles. presents previous research in a straightforward and comprehensive manner. The formulation of the problem in this study applies the Analytical Hierarchy Process (AHP) method in determining the level of stunting vulnerability (malnutrition) in Juhar District. How big is the result of applying the AHP method in determining the level of vulnerability to stunting (malnutrition) in Juhar District. designing and building a decision system using the Analytical Hierarchy Process (AHP) method in determining the level of stunting vulnerability (malnutrition) in the village of Juhar District based on web programming.